2017
DOI: 10.4168/aair.2017.9.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Resveratrol on Airway Remodeling by Transforming Growth Factor-β/Smad Signaling Pathway in Chronic Asthma Model

Abstract: PurposeAsthma is a chronic airway disease characterized by airway remodeling, leading to a progressive decline in lung function. Therapeutic agents that attenuate airway remodeling can complement the limited effects of traditional glucocorticoids. In this study, we investigated the effect of resveratrol on allergic airway inflammation and remodeling in a murine model of chronic bronchial asthma.MethodsPeribronchial smooth muscle thickening that developed in mice challenged with a 3-month repeated exposure to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 31 publications
(38 reference statements)
4
46
0
Order By: Relevance
“…Cell senescence in the lung is closely related to the pathogenesis of asthma. The senescence of airway epithelial cells is associated with the development of asthma, such as airway remodeling . Thus, our results strongly suggest that senescence of airway epithelial cells after ITGB4 deficiency may have a close relationship to the pathogenesis of asthma.…”
Section: Discussionsupporting
confidence: 54%
“…Cell senescence in the lung is closely related to the pathogenesis of asthma. The senescence of airway epithelial cells is associated with the development of asthma, such as airway remodeling . Thus, our results strongly suggest that senescence of airway epithelial cells after ITGB4 deficiency may have a close relationship to the pathogenesis of asthma.…”
Section: Discussionsupporting
confidence: 54%
“…However, among the patients with AERD, highFLCN was not directly associated with the features of AERD such as severe asthma, airway hyperresponsiveness and CRS/NPs, indicating that serum FLCN may not be directly associated with key clinical features, but contribute to aggravating the severity of airway inflammation in AERD, as AERD subjects with highFLCN had a higher serum TGF‐β1 level. TGF‐β1 is produced from various cells, in which eosinophil‐derived TGF‐β1 is the major source for provoking the epithelial to mesenchymal transition, hence worsening airway inflammation and remodelling …”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 is produced from various cells, in which eosinophil-derived TGF-β1 is the major source for provoking the epithelial to mesenchymal transition, hence worsening airway inflammation and remodelling. 25,26 We targeted epithelial cells, an abundant source of FLCN in order to evaluate its role in AERD. 17 The The role of FLCN in maintaining the integrity of epithelial barrier has been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…The natural sources of resveratrol are skin of grapes, several berries, and senna 5. In this issue, Lee et al6 reported the therapeutic effects of resveratrol in a murine model of allergic asthma. They showed that oral administration of resveratrol efficiently suppressed ovalbumin (OVA)-induced airway inflammation and remodeling.…”
mentioning
confidence: 99%
“…Interestingly, in this issue Lee et al6 showed that resveratrol treatment suppressed epithelial-mesenchymal transition (EMT) markers, such as snail, slug, vimentin, and α-SMA. EMT is known to be induced by various environmental factors, and oxidative stress is one of the main triggers of EMT.…”
mentioning
confidence: 99%